Cognitive and language performance predicts effects of spelling intervention and tDCS in Primary Progressive Aphasia. (March 2020) - de Aguiar, Vânia; Zhao, Yi; Ficek, Bronte N.; Webster, Kimberly; Rofes, Adrià; Wendt, Haley; Frangakis, Constantine; Caffo, Brian; Hillis, Argye E.; Rapp, Brenda; Tsapkini, Kyrana
Abstract: Predictors of treatment effects allow individual tailoring of treatment characteristics, thereby saving resources and optimizing outcomes. Electrical stimulation coupled with language intervention has shown promising results in improving language performance in individuals with Primary Progressive Aphasia (PPA). The current study aimed to identify language and cognitive variables associated with response to therapy consisting of language intervention combined with transcranial direct current stimulation (tDCS). Forty individuals with PPA received written naming/spelling intervention combined with anodal tDCS or Sham, using a between-subjects, randomized design, with intervention delivered over a period of 3 weeks. Participants were assessed using a battery of neuropsychological tests before and after each phase. We measured letter accuracy during spelling of trained and untrained words, before, immediately after, 2 weeks, and 2 months after therapy. We used step-wise regression methods to identify variables amongst the neuropsychological measures and experimental factors that were significantly associated with therapy outcomes at each time-point. For trained words, improvement was related to pre-therapy scores, in RAVLT (5 trials sum), pseudoword spelling, object naming, digit span backward, spatial span backward and years post symptom onset. Regarding generalization to untrained words, improvement in spelling was associated with pseudoword spelling, RAVLT proactive interference, RAVLT immediate recall. Generalization effects were larger under tDCS compared to Sham at the 2-month post training measurement. We conclude that, for trained words, patients who improve the most are those who retain for longer language skills such as sublexical spelling processes (phoneme-to-grapheme correspondences) and word retrieval, and other cognitive functions such as executive functions and working memory, and those who have a better learning capacity. Generalization to untrained words occurs through improvement in knowledge of phoneme-to-grapheme correspondences. Furthermore, tDCS enhances the generalizability and duration of therapy effects.